Association between Parenting Patterns and Exclusive Breastfeeding with Wasting Incidence in Toddlers - Malwani, Selma Aqila; Zulaikha, Fatma; Asthiningsih, Ni Wayan Wiwin (Genius Journal, 2025)
Introduction: Wasting is a form of acute malnutrition that significantly affects the physical growth, brain development, and immune function of toddlers. Various factors, including parenting styles and breastfeeding practices, may influence the occurrence of wasting. Objective: This study aims to analyze the relationship between parenting styles and exclusive breastfeeding with the incidence of wasting among toddlers in the Sidomulyo Health Center area, Samarinda City. Methods: A quantitative, correlational study with a cross-sectional design was conducted involving 168 toddlers aged 2–5 years, selected through stratified cluster sampling. Data were collected using structured questionnaires and analyzed using the Chi-Square test and Fisher’s Exact Test to assess the associations between variables. Results: The findings revealed that permissive parenting was associated with the highest proportion of wasting cases (46.2%), whereas democratic parenting showed the lowest proportion (9.9%). A significant relationship was found between parenting style and the incidence of wasting (p = 0.000). Furthermore, toddlers who were not exclusively breastfed had a significantly higher risk of wasting compared to those who received exclusive breastfeeding (p = 0.000). Conclusion: Maternal characteristics, parenting styles, and breastfeeding practices play a significant role in determining the nutritional status of toddlers. Democratic parenting and exclusive breastfeeding were found to contribute positively to the prevention of wasting.